Level of self-efficacy and the personal and societal resources of sentenced persons - Anna Danuta Wojnarska; Małgorzata Osińska (Maria Curie-Skłodowska University, Lublin, Poland, 2020)
The purpose of this article is to characterize personal resources of convicted individuals with different levels of self-efficacy. Sixty-six subjects were analyzed using self-efficacy, self-evaluation, stress management, resilience, and hope for success tests. Contrary to expectations, the convicts presented a fairly high level of self-efficacy. In terms of varying levels of this variable, low and moderate dependencies on four strategies of dealing with stress, resilience and hope for success were observed. Furthermore, the predictive model of the variable covered resilience, ability to find solutions and planning, justifying 48,0% of variance. Limitations and directions for further research are presented.